Hungarian Monitoring, 16 December 1988 . [Magyar rádiófigyelő], 1988. december 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Karabakh Committee account of Armenian earthquake - On Dubček's possible future role - Czechoslovak CP Central Committee session comes to a close in Prague Domestic Affairs: - Károly Grósz speaks at Miskolc Party activists' meeting - Minimum HUF 3,000 exchange amount to be abolished from January, more new customs and exchange measures decided upon - Draft law on assembly would not allow demonstrations in the direct vicinity of parliament - Péter Várkonyi's speech in Munich on traditional weapons reduction - Minister of state Imre Pozsgay informs Austrian chancellor on Hungarian reforms and government's activities Külpolitika: - Az örményországi földrengés a Karabah Bizottság beszámolójának tükrében - Dubček esetleges jövőbeni szerepéről - Prágában befejeződött a CSKP KB ülése Belpolitika: - Grósz Károly is felszólalt a miskolci pártaktíván - Januártól megszűnik a 3 ezer Ft-os kötelező valuta ellátási minimum. Több új vám - És devizaintézkedésről történt VI. Lenin döntés - A gyülekezésről szóló törvénytervezet szerint nem engedélyeznek tüntetést a parlament közvetlen környékén - Várkonyi Péter müncheni beszédében a hagyományos fegyverek csökkentéséről beszélt - A magyarországi reformokról és a kormányzat törekvéseiről tájékoztatta az osztrák kancellárt Pozsgay Imre államminiszter